DETERMINATION OF WATER SOLUBLE AND ETHANOL SOLUBLE CONTENT OF MATOA (Pometia pinnata J. R. Forst & G. Forst) LEAVES - Ellen Stephanie Rumaseuw; Febriana Imelda (Jurnal Kesehatan, 2023)
The matoa plant (Pometia pinnata J.R. & G.Forst) has been known to have many pharmacological effects and is used as traditional remedy. Matoa plants are recognized to contain secondary metabolites that have potential as medicine. One of the parts of matoa leaves that is traditonally as antibacterial, diuretic, analgesic and others. The quality of raw materials for traditional medicine is identified by the standardization. The standardization of implicial quality parameters is one of the specific parameters that test the water soluble implic and the ethanol soluble essence content. The reason of this observe become to determine water soluble essence and ethanol soluble essence content material on matoa leaf implicial. The take a look at uses an experimental approach. Matoa leaves were received through macerate extraction method the use of 2 types of solvents, specifically water solvent and 96% ethanol solvent. The effects showed that the water soluble essence and ethanol soluble essence values had been 15,81% and 27,72%.